Knowledge and attitude related to antibiotic use among high school students - Sharma, Manoj; Kaundinnyayana, Sammodavardhana; Das, Premlata (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Antibiotic resistance has been described by World Health Organisation as a major global health problem that threats our ability to treat common infectious diseases and needs urgent action. Among many other factors, knowledge and behaviour of community members that lead to inappropriate use of antibiotic highly contributes to development and spread of antimicrobial resistance. Hence this study has been undertaken with the aim to assess the knowledge and attitude related to antibiotic use among high school students. Methods: A cross-sectional questionnaire based survey was conducted at a Kathmandu based high-school. The data were collected via self-administered questionnaire after verbal consent for voluntary participation. There were nine questions related to knowledge and five questions related to attitude. Data were aggregated to compile frequency distribution tables and the percentages of responses were calculated. Result: A total of 232 students participated in the study. In the questions related to knowledge, nearly 62% of the students agreed to the statement “Antibiotics are needed to cure most coughs and cold”. About 19% students were not sure whether antibiotics can kill the useful bacteria in our body. In the attitude part, 53.87% students responded that they stop taking antibiotics when they start to feel better and 59.91% students responded that they buy antibiotics on their own from a pharmacist when needed. Conclusions: The deficiencies in basic understanding about the nature and use of antibiotics and casual attitude in their use among high school students is a matter of great concern as it poses many serious problems including promotion of antibiotic resistance